A case report of neurosyphilis coexisting with a positive MOG antibody manifested as optic neuritis - Shi, Min; Luo, Danqing; Li, Zhaoying; Li, Man; Jin, Shuoguo; Yang, Dongdong; Guo, Jun; Chen, Guo (Frontiers in Neurology, 2023)
Background Neurosyphilis refers to an infection of the central nervous system by Treponema pallidum. The clinical manifestations of neurosyphilis are diverse, making it easy to miss or misdiagnose. Anti-myelin oligodendrocyte glycoprotein antibody-associated disease is a recently defined immune-mediated inflammatory demyelinating central nervous system disease. Few studies have reported the coexistence of the two diseases. Case presentation This case report presents a 37 years-old male patient with neurosyphilis manifested as optic neuritis with a positive myelin oligodendrocyte glycoprotein (MOG) antibody. This patient received intravenous administration of 3.2 million units of procaine penicillin every 4 h for 2 weeks, followed by a two-week intramuscular injection of benzathine penicillin. Additionally, methylprednisolone sodium succinate was administered intravenously at 1,000 mg/day, gradually reduced to 500 mg/day and 240 mg/day every 3 days. Subsequently, prednisone tablets at a dosage of 60 mg/day were orally administered, with a gradual reduction of 5 mg/day every 3 days until reaching a dosage of 30 mg/day. The patient’s visual acuity was improved after 26 days of hospitalization. However, the visual field and color vision did not. At 3 months of follow-up, the symptoms remained unchanged despite the patient continued taking oral prednisone tablets at a dosage of 30 mg/day. Conclusion Neurosyphilis could be a potential triggering factor for MOGAD. In patients with neurosyphilis, it is strongly recommended to perform testing for MOG antibody along with other brain disease antibodies.